2015
DOI: 10.1016/j.physa.2014.07.086
|View full text |Cite
|
Sign up to set email alerts
|

New entropy formula with fluctuating reservoir

Abstract: h i g h l i g h t s• We present a mathematical procedure to obtain a deformed entropy function.• We describe effects due to finite heat capacity and temperature fluctuations in the heat reservoir.• For the Gaussian fluctuation model the resulting entropy-probability relation recovers the traditional ''log'' formula. • Without temperature fluctuations (but at finite heat capacity) we obtain the Tsallis formula.• For extreme large temperature fluctuations we obtain a new ''log(1 − log)'' formula. a b s t r a c t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 33 publications
1
45
0
2
Order By: Relevance
“…Since the (pseudo-)extensivity is more a characteristic property of the actual interaction/correlation between X and Y rather than entropy itself, we shall not dwell on this issue here. Let us just mention that the actual form of non-extensivity and the value of parameters can be often connected to some specific physical phenomena [8,22]. In Section 3, we will see that, from a strictly mathematical standpoint, it is logically more satisfactory to deal with dependent, but non-interacting systems.…”
Section: Some (Pseudo-)additivity Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the (pseudo-)extensivity is more a characteristic property of the actual interaction/correlation between X and Y rather than entropy itself, we shall not dwell on this issue here. Let us just mention that the actual form of non-extensivity and the value of parameters can be often connected to some specific physical phenomena [8,22]. In Section 3, we will see that, from a strictly mathematical standpoint, it is logically more satisfactory to deal with dependent, but non-interacting systems.…”
Section: Some (Pseudo-)additivity Rulesmentioning
confidence: 99%
“…The meaning of the chain rule (8) is depicted in Figure 1. By induction, one can generalize the previous relation (8) to:…”
Section: Entropic Chain Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the recently suggested doubly logarithmic entropy formula, designed for extreme large fluctuations in a reservoir by Biro et al [23,24], considers…”
Section: Entropic Distancementioning
confidence: 99%
“…Instead of treating the temperature or its inverse as a fluctuating quantity, one may also consider the number of degrees of freedom, and hence the dimensionality of phase space, as a fluctuating quantity. In [19][20][21][22][23] it has been shown that simple fluctuation patterns of the particle number, N, influencing the phase space volume Ω occupied by an ideal gas, can lead both to an exponential distribution of exp(−ω/T) by a Poisson N distribution, or to cut power-law like Tsallis-Pareto distribution by a negative binomial N distribution. In general, a trace form entropy,…”
Section: Introductionmentioning
confidence: 99%